Design and tests of a super real‐time simulation‐based power system real‐time decision‐making emergency control system. Issue 9 (20th March 2020) - Xiao, Tannan; Zou, Yu; Xia, Yanhui; Tong, Weilin; Gao, Yifan; Wang, Jianquan
Abstract : In many China's enterprise‐owned power grids (EPGs), the frequently changing operation state and the poor reliability of some outdated facilities may lead to inaccuracy or even malfunctions of the traditional pre‐decision‐making emergency control systems, which have already caused several blackouts in EPGs. To solve this problem, a real‐time decision‐making emergency control system based on the detailed time‐domain transient stability simulation is designed. Based on the trajectory characteristics of the stability restoration process of EPGs, the stability restoration criteria are proposed to significantly shorten the simulation time needed to judge the elimination of a certain stability problem. Fast decision‐making algorithms for frequency instability, rotor angle instability and branch overload with relatively low computational cost are introduced. Control strategies can be determined within a specific time after faults are detected. The corresponding countermeasures are directly executed when the strategy is obtained. The system configuration is designed to be capable of dealing with complicated and unanticipated faults, such as cascading outages and unexpected grid splitting. The test results of a 31‐node practical EPG show that the proposed algorithms and the system configuration are practical and efficient. This work is a meaningful exploration of the real‐time decision‐making emergency control system.